Insecticidal Effect of Lemongrass Essential Oil Against Megalurothrips usitatus (Bagnall) - Yun Han; Ming Zhu; Bo Qiu; Shaukat Ali; Jianhui Wu (Agronomy)
Megalurothrips usitatus is a global pest damaged legume crops, particularly cowpea (Vigna unguiculata). This study aimed to determine the chemical composition of lemongrass essential oil (LEO) and its insecticidal activity against the insect pest M. usitatus. The composition of lemongrass essential oil was analyzed using Gas Chromatography Mass Spectrometry (GC-MS). D-limonene, Neral, and Citral were found to constitute over 30% of the essential oil. LEO exhibited higher insecticidal toxicity than the individual pure components. Based on our results, the optimal formulation of LEO emulsifiable concentrates (ECs) was identified, and their insecticidal activity was further investigated. The mortality rate induced by the LEO did not significantly differ from that of the emamectin benzoate (EB) formulation but was lower than that of spinosad (SP). Additionally, LEO was shown to act as a synergist when combined with EB for controlling M. usitatus. This research offers an alternative strategy for controlling M. usitatus and reducing the reliance on synthetic pesticides.